Anti-adaptors use distinct modes of binding to inhibit the RssB-dependent turnover of RpoS (σS) by ClpXP - Micevski, Dimce; Zammit, Jessica E.; Truscott, Kaye N.; Dougan, David A. (Frontiers in Molecular Biosciences, 2015)
In Escherichia coli, σS is the master regulator of the general stress response. The level of σS changes in response to multiple stress conditions and it is regulated at many levels including protein turnover. In the absence of stress, σS is rapidly degraded by the AAA+ protease, ClpXP in a regulated manner that depends on the adaptor protein RssB. This two-component response regulator mediates the recognition of σS and its delivery to ClpXP. The turnover of σS however, can be inhibited in a stress specific manner, by one of three anti-adaptor proteins. Each anti-adaptor binds to RssB and inhibits its activity, but how this is achieved is not fully understood at a molecular level. Here, we describe details of the interaction between each anti-adaptor and RssB that leads to the stabilization of σS. By defining the domains of RssB using partial proteolysis we demonstrate that each anti-adaptor uses a distinct mode of binding to inhibit RssB activity. IraD docks specifically to the N-terminal domain of RssB, IraP interacts primarily with the C-terminal domain, while IraM interacts with both domains. Despite these differences in binding, we propose that docking of each anti-adaptor induces a conformational change in RssB, which resembles the inactive dimer of RssB. This dimer-like state of RssB not only prevents substrate binding but also triggers substrate release from a pre-bound complex.